ENERGY ASSESSMENT OF DIFFERENT RICE-BASED CROPPING SYSTEMS UNDER IRRIGATED CONDITION OF EASTERN UTTAR PRADESH, INDIA - MANOGNYA (African Journal of Environmental Economics and Management, 2021)
In an on-farm field experiment conducted over the consecutive years of 2021–23 at Kumarganj, Ayodhya, Uttar Pradesh, ten different rice -based crop sequences were evaluated for their performance inform of energy input- output dynamics, energy use efficiency productivity and sustainability. The sequences included: rice-wheat-fallow, rice-wheat-greengram, rice-frenchbean-greengram, rice-gram-cowpea, rice-mustard-greengram, rice-linseed- blackgram, rice-berseem-sudanchari, rice-cowpea-oat-maize + cowpea, rice-cauliflower-okra, and rice-potato- cowpea (vegetable). Among these, rice-potato-cowpea (vegetable) sequence had the highest energy input at 53.58 x 10³ MJ/ha. However, the maximum energy output was achieved with fodder-based rice cropping systems, recording 341.02 x 10³ MJ/ha during first year and 331.84 x 10³ MJ/ha in the second year. The highest energy use efficiency was observed in rice-oat-maize+cowpea and rice-berseem-sudanchari systems for both years. The se- quence of rice-oat-maize+cowpea not only demonstrated the highest energy output efficiency at 1033 but also pro- vided the greatest energy net return of 299 x 10³ MJ/ha and the highest energy intensity at 3.89 MJ/Rs. This was closely followed by rice-berseem-sudanchari sequence, which achieved an energy output efficiency of 941, an en- ergy net return of 288 x 10³ MJ/ha, and an energy intensity of 3.42 MJ/Rs. When considering the combination of energy input, energy output, energy use efficiency, and energy output efficiency, the rice-oat-maize+cowpea se- quence emerged as the most effective among the ten crop sequences tested. This sequence offers a comprehen- sive advantage by maximizing energy efficiency and economic returns, making it the best choice for the specific conditions of the experiment.